2007
DOI: 10.1002/hed.20561
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of MMP‐2 and MMP‐9 in patients with oral cancer

Abstract: The data indicate that MMP-2 and MMP-9 can be useful to identify metastatic phenotype as well as for treatment monitoring in oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 28 publications
7
90
0
10
Order By: Relevance
“…Our data suggest that one mechanism by which FLJ10540 may promote tumor cell migration and invasion is through the increased expression and proteolytic activity of MMP-2, which specifically degrades the basement membrane (Figure 7a). The MMP-2 has been suggested to play critical roles in oral cancer migration and metastasis (Munshi et al, 2002;Ruokolainen et al, 2006;Patel et al, 2007), and the upregulation of MMP-2 has been associated with a poor prognosis in oral cancer patients (Ruokolainen et al, 2006). The activation of proMMP-2 has been considered to be a particularly important step in tumor invasion (Itoh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that one mechanism by which FLJ10540 may promote tumor cell migration and invasion is through the increased expression and proteolytic activity of MMP-2, which specifically degrades the basement membrane (Figure 7a). The MMP-2 has been suggested to play critical roles in oral cancer migration and metastasis (Munshi et al, 2002;Ruokolainen et al, 2006;Patel et al, 2007), and the upregulation of MMP-2 has been associated with a poor prognosis in oral cancer patients (Ruokolainen et al, 2006). The activation of proMMP-2 has been considered to be a particularly important step in tumor invasion (Itoh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 is also closely associated with tumor progression and metastasis in human OCSCC; specifically, they have been shown to be localized to the advancing tumor front and are implicated in metastatic dissemination (Hong et al, 2000). The elevated expression of the MMP-2 immunoreactive protein is correlated with a poor prognosis in OCSCC (Ruokolainen et al, 2004;Gao et al, 2005;Patel et al, 2007). In addition, MMP-2 expression could be regulated by several transcription factors, including YB-1 (Mertens et al, 1997), Sp1 (Qin et al, 1999), p53 (Bian and Sun, 1997), Stat3 (Xie et al, 2004) and FOXM1 (Dai et al, 2007); however, the molecular mechanisms by which MMP-2 is activated and controls tumor metastasis in OCSCC remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The cleavage of laminin-5 by MMP-2 and MMP-14 reveals its matricryptic site (hidden forms of extracellular matrix molecules that can be exposed by structural modifications), favoring cell motility. 22 Patel et al 23 evaluated the expression of MMP-2 and 9 and the plasma concentration of these gelatinases in tissue samples with malignant lesions. The authors suggested that the expression of these MMPs could be a useful diagnostic marker in the detection and monitoring of malignant lesions, given that tissue expression of these enzymes was shown to be high in these lesions and in the plasma.…”
Section: Zinc and Metalloproteinases Of The Extracellular Matrixmentioning
confidence: 99%
“…Verrucous carcinoma (VC) is considered to be an uncommon exophytic distinctive low-grade well differentiated pathological variant of OSCC (3) . Cancer is a multifactorial, multifaceted, and multimechanistic disease requiring a multidimensional approach for its diagnosis, treatment, and prevention (4) . Over the past decade, several studies have shown that the microenvironment or stroma of neoplastic tissues plays an active role in tumor progression.…”
Section: Introductionmentioning
confidence: 99%